Auditoría Tributaria aplicada a la Compañía de Transporte Mixto Pucayacu en el cantón La Maná, provincia de Cotopaxi período 2021. - Cujilan Oña, Jennifer Yomaira (2023)
The investigation carried out had as its main objective the determination of tax compliance of the Compañía Transporte Mixto Pucayacu, period 2021. Being the main problem existing within the mentioned company, it focused on the lack of organization of documents associated with the monthly and annual tax returns of the company. organization; likewise, the application of the tax regulations in an inappropriate manner without considering the latest updates associated with the aforementioned topic. The methodology applied for the execution of this inquiry was framed in a qualitative approach, under the implementation of the types of field research, Descriptive. Likewise, the analysis-synthesis method was applied. Regarding the data collection techniques, both observation and interview were applied; through the collection instruments established as the observation guide and the questionnaire. During the development of the study, a tax audit was applied, the main theme of which was focused on the tax audit applied to the Pucayacu Mixed Transport Company in the La Maná canton province of Cotopaxi, period 2021. The main objective of the aforementioned audit was to execute a tax audit in the Mixed Transport Company Pucayacu S.A. for verification of the processes associated with both monthly and annual tax returns made in the 2021 period; which was divided into four elementary phases, the first being preliminary knowledge; followed by phase two focused on planning; thirdly, the execution phase and finally, the communication of the results. Among the main conclusions generated in the audit process carried out was the lack of an adequate accounting process; as well as, the unpunctual payment of value added taxes as well as income taxes generates fines by the SRI. Consequently, the existence of some contradictions regarding the administrative and organizational focus of the Company was evidenced. Regarding the general conclusions of the investigation, during the diagnostic process carried out through the interview technique, the members of the management personnel of the company subject to investigation stated that both monthly and annual declarations are executed; as well as the development of the financial statements by the external accountant. Likewise, each of these accounting elements is kept organized and updated. In addition, they affirmed that if they develop such compliance before the SRI, being the fiscal body responsible for tax collection. While, during the process of execution of the tax audit, a value of fine for non-compliance was evidenced on the corresponding payment date.